Pelatihan Penggunaan Reference Manager untuk Meningkatkan Pengolaan Sitasi dan Daftar Pustaka Karya Tulis Ilmiah Mahasiswa - Nur, Muhammad Awal Nur; Asriadi; Ainun Oktaviani; Muhammad Ikhsan Sukaria; Muhammad Idris Jafar (JCSE: Journal of Community Service and Empowerment, 2025)
Low student understanding of citation management and bibliography formatting is a common obstacle in academic writing. Many students still compile references manually without following standardized styles such as APA Style, which can reduce academic quality and increase the risk of plagiarism. In response to this issue, this community service activity aims to improve students’ skills in managing citations and references digitally through training on the use of reference manager applications such as Mendeley and Zotero. The training was conducted face-to-face on February 22, 2025, at PGSD UNM Bone Campus and was attended by 85 students. The training method included material presentations, hands-on practice, and evaluation. The results showed that most participants experienced increased understanding and ability in inserting citations and generating bibliographies automatically. This training has proven to positively impact the development of more systematic and academically sound student writing. It is expected that similar activities will be implemented regularly to foster a strong academic culture.